Pengaruh Current Ratio, Return on Equity Dan Inventory Turnover Terhadap Earning Pershare Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2020 - Stevani; Latersia Br Gurusinga (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2022)
This study aims to examine and analyze the effect of the current ratio, return on equity and inventory turnover having an effect on earnings per share in mining sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The research method used in this study uses quantitative research methods with quantitative descriptive research that is explanatory research. The population of this research is all large trading and small trading sub-sector companies listed on the Indonesia Stock Exchange totaling 43 companies. The sample of this research is 15 companies with purposive sampling technique. The results of the research show that partially current ratio has an effect on earnings per share, the rest on return on equity and inventory turnover have no effect on earnings per share. Simultaneously current ratio, return on equity and inventory turnover affect earnings per share